Peningkatan Karakter Semangat Belajar melalui Metode Make A Match di MTsN 2 Kota Palangka Raya - Aditya Fauzianur Adit; Ahmad Saefulloh Ahmad Saefulloh (Yayasan Azhar Amanaa Yogyakarta, 2023)
This study aims to determine the increase in interest in learning PPKn through the make a match method in class IX students of MTsN 2 Palangka Raya City in the 2022/2023 academic year. The subjects of this classroom action research were 32 students in class IX MTsN 2 Palangka Raya City for the 2022/2023 academic year. Methods of data collection using observation, tests and documentation. The results of the research show that learning through the make a match method can increase students' interest in learning, active participation of students in learning and students' abilities